2018
DOI: 10.1097/jac.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

How 6 Organizations Developed Tools and Processes for Social Determinants of Health Screening in Primary Care

Abstract: Little is known about how healthcare organizations are developing tools for identifying/addressing patients’ social determinants of health (SDH). We describe the processes recently used by six organizations to develop SDH screening tools for ambulatory care, and the barriers they faced during those efforts. Common processes included reviewing literature and consulting primary care staff. The organizations prioritized avoiding redundant data collection, integrating SDH screening into existing workflows, and add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
152
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 21 publications
0
152
0
Order By: Relevance
“…The SDH domains themselves continue to be redefined as health care organizations strive to create comprehensive screening tools. 29 Further progress requires screening tools that cover multiple domains but are sensitive, valid and concise. While our understanding of the harms of adverse SDH grows, we need to continue to gather evidence showing which primary care initiatives truly improve health outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SDH domains themselves continue to be redefined as health care organizations strive to create comprehensive screening tools. 29 Further progress requires screening tools that cover multiple domains but are sensitive, valid and concise. While our understanding of the harms of adverse SDH grows, we need to continue to gather evidence showing which primary care initiatives truly improve health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In response to this inconsistency in the availability and usability of tools, health care organizations are developing comprehensive screening tools covering an array of SDH domains. 29 The Institute of Medicine has identified 11 potential SDH domains for inclusion in the electronic health record. 29 Positive SDH screens call for referral and linkage to resources with follow up and care coordination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have documented the challenges of effectively using information from self-reported screening instruments on social determinants of health such as housing instability. [20][21][22][23][24] These challenges fall into two broad categories: (a) determining how to resolve the logistical, resource, and workload issues associated with the collection of information about housing instability and other social factors from patients; and (b) optimizing procedures for taking action on such information. With respect to the first set of challenges, evidence suggests that workload concerns are barriers to the effective implementation of screening tools.…”
Section: Byrne Et Almentioning
confidence: 99%
“…The HSCR is part of an ambitious primary prevention approach to address housing instability; however, the existence of the HSCR alone is insufficient to improve housing stability. Prior studies have documented the challenges of effectively using information from self‐reported screening instruments on social determinants of health such as housing instability . These challenges fall into two broad categories: (a) determining how to resolve the logistical, resource, and workload issues associated with the collection of information about housing instability and other social factors from patients; and (b) optimizing procedures for taking action on such information.…”
Section: Introductionmentioning
confidence: 99%